NK cell function and receptor diversity in the context of HCV infection - Gardiner, Clair M. (Frontiers in Microbiology, 2015)
Hepatitis C virus (HCV) infects over 170 million people in the world. While a minority of individuals are able to naturally clear this hepatotropic virus using their immune system, most people go on to develop a lifetime chronic infection that can result in severe liver pathology, potentially leading to liver cirrhosis and hepatic cellular carcinoma. Investigations into acute immune responses and spontaneous clearance of the virus are severely hampered by difficulties in identification of relevant patient cohorts. While the role for the adaptive immune response in viral clearance is well established, it is becoming clear that the innate immune system also impacts on HCV outcome. The innate immune response to infection is likely to influence the type of adaptive immune response that develops and will ultimately influence if the virus is cleared or develops into a chronic infection. Natural Killer (NK) cells are lymphocytes that have important anti-viral functions including direct cytotoxicity of infected cells and the production of inflammatory cytokines, e.g., IFN-γ. They are generally considered to be cells of the innate immune system, although there is increasing evidence that NK cells adapt and persist in response to particular viral infections. NK cells are altered in patients with acute and chronic HCV infection. There is increasing evidence from both cellular and genetic studies that NK cells modulate HCV outcome. This review will describe and discuss the current experimental and clinical evidence of a role for NK cells in HCV infection and describe recent discoveries that are likely to play a role in future research.